2017
DOI: 10.5897/ajps2017.1529
|View full text |Cite
|
Sign up to set email alerts
|

Curvularia lunata as, a dominant seed-borne pathogen in Dalbergia sissoo Roxb: Its location in seed and its phytopathological effects

Abstract: Dalbergia sissoo (shisham) seeds naturally infected with Curvularia lunata showed either black discoloration (1.25 to 8.75%) or appeared dull (0.50 to 10.0%). When they were incubated, they yielded pure growth of the pathogen. During location studies, cleared whole mount preparation and component plating revealed the presence of infection restricted to the seed coat and cotyledons of asymptomatic seeds. However, this pathogen penetrates the deeper tissue of symptomatic seeds to the embryonic axis. Due to heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Curvularia spp. are internally and externally seed-borne pathogenic fungi, affecting seed germination and seedling vigour, known to be responsible for pre-and post-emergence seedling mortality (Gupta et al, 2017). They cause seed disclouration, even produce toxins that may be injurious to man and domestic animals.…”
Section: Introductionmentioning
confidence: 99%
“…Curvularia spp. are internally and externally seed-borne pathogenic fungi, affecting seed germination and seedling vigour, known to be responsible for pre-and post-emergence seedling mortality (Gupta et al, 2017). They cause seed disclouration, even produce toxins that may be injurious to man and domestic animals.…”
Section: Introductionmentioning
confidence: 99%
“…Curvularia species such as C. lunata had been previously reported in seeds of Coix lacryma-jobi (Kim & Lee 1998), Andropogon sp. (Santos et al 2018), Dalbergia sissoo (Gupta et al 2017), and Solanum lycopersicum in Pakistan (Iftikhar et al 2016). This study first reported C. aeria associated from seeds of cherry tomatoes (Solanum lycopersicum var.…”
Section: Discussionmentioning
confidence: 99%